2012
DOI: 10.1155/2012/195367
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Administration of Oil Palm (Elaeis guineensis) Leaves Extract Attenuates Hyperglycaemic-Induced Oxidative Stress and Improves Renal Histopathology and Function in Experimental Diabetes

Abstract: Oil palm (Elaeis guineensis) leaves extract (OPLE) has antioxidant properties and because oxidative stress contributes to the pathogenesis of diabetic nephropathy (DN), we tested the hypothesis that OPLE prevents diabetes renal oxidative stress, attenuating injury. Sprague-Dawley rats received OPLE (200 and 500 mg kg−1) for 4 and 12 weeks after diabetes induction (streptozotocin 60 mg kg−1). Blood glucose level, body and kidney weights, urine flow rate (UFR), glomerular filtration rate (GFR), and proteinuria w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 57 publications
2
6
0
1
Order By: Relevance
“…Traditional use of leaf extract has led to its study for wound‐healing and antimicrobial properties (Chong et al ., ; Sasidharan et al ., ; Sasidharan, Logeswaran & Latha, ), and the role of its antioxidants in treating disease (e.g. diabetes; Rajavel et al ., ). Anecdotally, a variety of uses have been ascribed to oil palm, including all parts of the plant (Opute, ; Caniago & Siebert, ; Chong et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Traditional use of leaf extract has led to its study for wound‐healing and antimicrobial properties (Chong et al ., ; Sasidharan et al ., ; Sasidharan, Logeswaran & Latha, ), and the role of its antioxidants in treating disease (e.g. diabetes; Rajavel et al ., ). Anecdotally, a variety of uses have been ascribed to oil palm, including all parts of the plant (Opute, ; Caniago & Siebert, ; Chong et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…The juice squeezed from oil palm leaves can be applied on wounds to enhance healing while the sap is used as laxative, and in fermented form is effective for improving lactation in nursing mothers [56]. Leaf extract is also useful in treating diabetes [67]. Dropping infusion of young leaf of E. guineensis on affected part of body is useful for ear-ache of Idoma people, Benue State, Nigeria [50].…”
Section: Frondsmentioning
confidence: 99%
“…Osim et al (1994) had already shown that chronic consumption of thermoxidized palm oil destroys kidney tissues. There is evidence that the tocotrienol rich fraction (TRF) of fresh palm oil protects against renal injury (Rajavel et al 2012;Nowak et al 2012). Therefore TRF could have contributed to the normal GFR of the fresh palm oil-treated group, while the lack of TRF in the TPO and PPO may have contributed to the reduced GFR in these study groups.…”
Section: Discussionmentioning
confidence: 98%